Proposição de um método para análise da tomada de decisão em ações ofensivas no basquetebol - Gois Júnior, Luiz Eduardo Mello de (2014)
INTRODUCTION: basketball players must use logic to make decisions and perform appropriate actions in relation to the elements of the sport. One way to assess decision making (TD) is the match analysis, which is a strategy widely used in the sports science. Some studies used videos or photos for athletes to analyze the play and inform what they would do if those same actions happened during a match. This type of study excludes some elements present in game situations mischaracterizing the actual context and the keeping off of the variables that interfere with the game. To minimize this mischaracterization some authors used observational methodology, which uses observation of games filmed for evaluating TD during the match, ie, within the actual context of the game, and endeavoring to preserve the ecological validity. However, there is a lack of a validated instrument that describes the actions to be observed during matches, and thus guide the assessment of TD by teachers and coaches in the game-like situation context. OBJECTIVE: to propose a user-friendly tool to guide the evaluation of decision making of basketball athletes. METHODS: the sample consisted of 18 experienced basketball coaches (level III of National School of Basketball Coaches), 42.3 ± 11.1 years old. At first, a guide containing 30 real game situations was created, divided into five categories (dribbling, shooting, driving, player movement without the ball, and passing). Subsequently, coaches answered an on line survey to assess situations as right or wrong. Agreement was analyzed by the percentage of identical responses among coaches for each action. Three levels were considered: high (between 80 % and 100 %), moderate (between 70 % and 79 %) and low agreement (50 % and 69 %). Furthermore, a computerized worksheet for analysis was created. Three national level experienced coaches were invited to test the operational feasibility of the worksheet. Coaches individually watched a video with 20 consecutive ball possessions of the same team during the 2010 Adult Sergipe State Championship final match, and then answered a questionnaire about the use of the worksheet. RESULTS: All "Dribbling" actions had high agreement (83 % to 100 %). The "shooting" category had four actions with high agreement (94% to 100%), two with moderate (both 78%) and one had a low degree of concordance (67%). In the "Driving category, three had high agreement (94% and 100%) and one had low agreement (56%). The categories "Player movement without the ball" and "Passing" obtained high agreement on all actions (94% to 100% and 89% and 100%, respectively). All three coaches consider the worksheet to be feasible, becoming easier after a brief familiarization period. CONCLUSION: actions defined for each category proved to be valid to be part of the evaluation guide of TD, and the use of the worksheet was feasible from an operational standpoint.